2006
DOI: 10.1159/000095309
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Knockout Mice Over-Expressing Human Tissue Inhibitor of Metalloproteinase 1 Are Protected against Aneurysm Formation but Not against Atherosclerotic Plaque Development

Abstract: Aims: We investigated the effect of plasma levels of human tissue inhibitor of metalloproteinase (hTIMP)-1 on arterial lesion development and aneurysm formation in apolipoprotein-E-deficient mice (ApoE–/–). Methods: Control and transgenic mice were fed either a chow diet or a high-fat diet for 90 and 180 days. Results: hTIMP-1 has a tendency to decrease atherosclerotic lesions, but did not attain significance (approximately 6% reduction in hTIMP-1+/+, p = 0.075, and approximately 4% in hT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…TIMP-1 message was significantly higher in proximal vs distal regions (Figures 2, 4) and TIMP-1 protein localized to macrophages (Figure 7). This is consistent with reports that TIMP-1 overexpression does not alter plaque stability [20]. TIMP-4 mRNA was low and similar in both regions (Figure 2).…”
Section: Resultssupporting
confidence: 93%
“…TIMP-1 message was significantly higher in proximal vs distal regions (Figures 2, 4) and TIMP-1 protein localized to macrophages (Figure 7). This is consistent with reports that TIMP-1 overexpression does not alter plaque stability [20]. TIMP-4 mRNA was low and similar in both regions (Figure 2).…”
Section: Resultssupporting
confidence: 93%
“…In in vivo studies, let-7g levels were found reduced both in high-fat diet mice and hypercholesterolemia humans, in accordance with in vitro results [60]. Let-7d and let-7i levels are down-regulated in CAD patients [27,64], and let-7s are up-regulated in patients suffering atherosclerotic abdominal aortic aneurysm (AAA) [65].…”
Section: Let-7 In Cardiovascular Diseasesmentioning
confidence: 59%
“…When transgenic mice overexpressing TIMP-1 were cross-bred with ApoE-null mice, there was no difference in lesion area compared to ApoE-null controls. 108 Two independent studies of mice with targeted deletion of TIMP-1 on the ApoE-null background also report contradictory results; plaque formation was either decreased 109 or not changed. 110 By contrast, overexpression of TIMP-2 by systemic injection of adenovirus inhibited plaque growth by decreasing macrophage invasion; however, SMC number and collagen and elastin content were increased.…”
Section: Collagens and Atherosclerotic Complicationsmentioning
confidence: 99%